PENERAPAN METODE BimCaBel JPBB (JANGAN PERNAH BERHENTI BERTANYA) UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA - suhardi suhardi (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2020)
The purpose of this study is to improve student achievement in grades VIII 2 and VIII.3 in the odd semester of the 2019/2020 academic year through the JPBB BimCaBel method. This research activity was carried out at Tanete Riaja Middle School 2 with the target class of action being students of class VIII, namely classes VIII.2 and VIII.3. Class VIII students who are targeted in this activity are students who have many challenges in terms of different student learning styles. The research procedures including data analysis used in this research activity is to use comparative analysis through 2 action cycles. The results of the study showed that students showed a better or improved level of mastery of the material using JPBB learning techniques and besides that it showed an optimistic and confident attitude that would support their success in their current and future educational processes.